The Effectiveness of the National Unity and Politics Agency of Karawang Regency in Fostering Community Organizations - Nur Setiawati, Febri; Ramdani, Rachmat; Deby Mahendra Putri, Lolita (Journal of Government Insight, 2025)
Community organizations are organizations founded by the community voluntarily with certain goals that are social, religious, cultural or common interests. Community organizations have an important role as a forum for community aspirations, social services, and strengthening involvement in the world of politics to build the nation. Conflicts that occur between social organizations can cause divisions between organizations in the future. This research aims to solve a problem that will be researched, therefore researchers in this research use descriptive methods with a qualitative approach. This research uses the theory of Organizational Effectiveness according to Duncan in Richard M. Steers (2003) with indicators of goal achievement, integration and adaptation. The results of this research are that conflicts that occur in Karawang Regency can cause divisions between organizations. suggests that the National Unity and Politics Agency prioritize training activities to avoid conflicts between organizations in the future. Training and coaching provided to organizational representatives in conflict management. Evaluation of the extent to which these skill improvements contribute to reduced conflict as well as increased collaboration between organizations could be a major focus in future studies.